2018
DOI: 10.1111/hel.12502
|View full text |Cite
|
Sign up to set email alerts
|

The “three‐in‐one” formulation of bismuth quadruple therapy for Helicobacter pylori eradication with or without probiotics supplementation: Efficacy and safety in daily clinical practice

Abstract: The three-in-one BQT is highly effective and well tolerated for H. pylori eradication in daily clinical practice. Probiotics supplementation fails to improve compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
46
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 21 publications
(70 reference statements)
4
46
2
2
Order By: Relevance
“…In recent large multicenter studies, elaborate re‐education is generally instructed throughout the trial to achieve high H pylori eradication rate, with patients’ adherence around 94%, sometimes even 100% . However, most studies performed in China revealed that the compliance during H pylori eradication is unpleasant in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent large multicenter studies, elaborate re‐education is generally instructed throughout the trial to achieve high H pylori eradication rate, with patients’ adherence around 94%, sometimes even 100% . However, most studies performed in China revealed that the compliance during H pylori eradication is unpleasant in clinical practice .…”
Section: Discussionmentioning
confidence: 99%
“…Previous study in our hospital showed the clarithromycin resistance rate in Shandong province had reached around 30%. As resistance to clarithromycin in China rapidly develops in last decades, some researchers proposed that the choice of clarithromycin‐containing regimen should rely on local resistance patterns and personal medical history …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are summarized inTable 2 52,53. No significant difference between the eradication rates was achieved by both regimens (86% vs 87%).…”
mentioning
confidence: 91%